Escape from fear - Martin A. Bursten. (Syracuse University Press, 1958)
Discusses also the role of Radio Free Europe broadcasts. The Freedom Fighters.--Neutral Austria.--America Steps In.--Dawn at the Border.--"J'accuse".--Homes - Not Camps.--From a Notebook.--No Trees in Kilmer.--The Golden Door.--The Future.